Program Pembinaan Kematangan Intelektual Pada Siswa SMA - Islam, Ahmad Chairul; Indra, Hasbi (Tawazun: Jurnal Pendidikan Islam, 2022)
The purpose of this research is to formulate a coaching program that is able to help the development of intellectual maturity in students, so that students are able and brave to make decisions objectively and solve problems based on their reason and conscience and by considering the consequences they will receive later, both in terms of learning, social, personal and career. This research uses descriptive qualitative research, with data collection techniques in-depth interviews, observations, document studies, processed with data analysis techniques Miles and Huberman models in the form of data collection, data reduction, data presentation, and verification of conclusion drawing. The result of this research is the intellectual maturity development program for high school students is carried out with a learning system in the classroom and also outside the classroom. Learning in the classroom is carried out 2 times for 1 week, and outside the class 1 meeting is equal to 2 hours of learning in class. The coaching program in the classroom is self-introduction, motivational training and moral aqidah. While the coaching activities outside the classroom are individual coaching, extracurricular, scouting and career days. Abstrak Tujuan penelitian ini, guna merumuskan program pembinaan yang mampu membantu perkembangan kematangan intelektual pada siswa, sehingga para siswa mampu dan berani untuk mengambil keputusan secara objektif dan menyelesaikan masalah berdasarkan akal dan hati nuraninya serta dengan mempertimbangkan konsekuensi yang akan diterimanya nanti, baik dalam aspek belajarnya, sosialnya, pribadinya dan juga kariernya. Penelitian ini menggunakan jenis penelitian kualitatif deskriptif, dengan teknik pengumpulan data wawancara mendalam, observasi, kajian dokumen, diolah dengan teknik analisis data model Miles dan Huberman berupa, pengumpulan data, reduksi data, penyajian data, dan verification penarikan kesimpulan. Hasil dari penelitian ini adalah Program pembinaan kematangan intelektual pada siswa SMA dilaksanakan dengan sistem pembelajaran di dalam kelas dan juga di luar kelas. Pembelajaran di dalam kelas dilakukan 2 kali pertemuan selama 1 pekan, dan di luar kelas 1 kali pertemuan sama dengan 2 jam pembelajaran di dalam kelas. Program pembinaan di dalam kelas yaitu pengenalan diri, training motivasi dan akidah akhlak. Sedangkan kegiatan pembinaan di luar kelas yaitu pembinaan perorangan, ekstrakurikuler, kepramukaan dan career day.